Analisis Frasa Eksosentris Dalam Novel Guru Aini Karya Andrea Hirata Dan Implikasinya Terhadap Pemahaman Pembelajaran Teks Ulasan Bahasa Indonesia Di Kelas Vlll SMP Negeri 4 Medan - Saragi, Novani; Panggabean, Sarma; Br.Sianipar, Vina Merina (Jurnal Kajian Ilmu Pendidikan (JKIP), 2024)
The aim of this research is to describe: (1) exocentric phrases in Guru Aini by Andrea Hirata, (2) describe the most dominant types of exocentric phrases in the novel Guru Aini by Andrea Hirata, (3) describe the implications of exocentric phrases in the novel Guru Aini by Andrea Hirata regarding learning Indonesian review texts in class VIII of SMP Negeri 4 Medan. This type of research is qualitative. The object studied in this research is the exocentric phrase in the novel Guru Aini by Andrea Hirata and its implications for understanding the learning of Indonesian review texts. The data for this research are sentences in the novel Guru Aini by Andrea Hirata which contain exocentric phrases. The data collection technique in this research uses reading and note-taking techniques. Researchers in this study analyzed exocentric phrases, dominant exocentric phrases, and the implications for learning Indonesian review texts in class VIII. Exocentric phrases can be classified into two groups, namely directive exocentric phrases and non-directive exocentric phrases. The researchers found 1,295 directive exocentric phrases and 388 nondirective exocentric phrases. From this data, the most dominant exocentric phrases are directive exocentric phrases. The implications for understanding review text learning in class VIII SMP Negeri 4 Medan, students understand learning to review literary works, namely Teacher Aini’s novel, and students can write review texts well.